A kinetics-based decomposition approach to reveal the nature of starch asymmetric gelatinization thermograms at non-isothermal conditions. (15th May 2021) - Li, Cheng; Hu, Yiming
Highlights: Starch gelatinization kinetics under non-isothermal conditions was investigated. A kinetics-based mathematical model was developed. The model yielded DSC endotherms that are essentially the same as experimental ones. The model can decompose DSC thermograms into kinetics-based sub-components. Different starches possess thermodynamically distinct sub-groups of crystallites. Abstract: Starch gelatinization under non-isothermal conditions with limited moisture content is a common industrial process involved in the processing of many starchy foods, while the nature of its asymmetric differential scanning calorimetry thermograms is still undefinable. This study for the first time developed a kinetics-based mathematical model, which could yield a parameterization of gelatinization thermograms that are essentially the same as experimental ones. Even more, the model is capable of decomposing gelatinization thermograms into kinetics-based sub-patterns, and revealing hidden features. By applying this newly developed methodology to nine starches with different plant origins and correlated with their lamellar structures, the results indicated that distinctly arranged groups (sub-components) of semi-crystalline lamellae with different thermal stabilities are existed in the native starch granules. This gives ways to better understand starch structure-property relations, and suggests useful directions for food manufactures to produce functional foods by understanding and differentially controlling the starch gelatinization sub-components.